Unele aspecte privind aplicarea legislaţiei de protecţie a concurenţei în România - Gheorghe Oprescu (Romanian Journal of European Affairs, 2003)
Romania is trying for some time to launch the deregulation and liberalization processes, absolutely necessary for economic development. Unfortunately, many persons in Romania consider competition as a harmful force, the cause of the hardships faced by indigenous firms. Our analysis will show that competition is indeed harmful not to all but only to inefficient firms. The role assigned to competition policy is to cure market failures. These failures may spring from two sources: business activity and government regulation. The former cause of monopoly and inefficiency is dealt with by legislation, the latter by lobbying decision-makers.